An energy-saving hydraulic servo system with safety consideration for pipe fatigue tests. (August 2014) - Xu, Bing; Cheng, Min; Yang, Huayong; Zhang, Junhui
This article proposes an energy-saving hydraulic servo control system to output axial tension forces under cyclical disturbances in pipe fatigue tests. A hydraulic accumulator and a single-chamber control method were utilized to recover the energy generated by the external disturbance. For the increased potential hazard of pipe fracture in the proposed system, a parameter selection method was discussed, which also considered desired force control accuracy and low energy consumption. A proportional–integral–derivative controller with a model-based feedforward compensator was designed to achieve good force control performance. The mathematical and simulation models of the proposed system were established, and the simulation results indicated that the proposed system could achieve the desired force control accuracy. The energy consumption of the proposed system could be reduced by 71.0% in contrast to that of the traditional system in a case study. Also, the simulation results indicated that the control performance was robust to uncertainties of the disturbance noises, the effective bulk modulus, the internal leakage coefficient of the cylinder and the adiabatic gas rate.